Between Political Arena and the Mosque: Islamist Governance in Egypt and Tunisia after the 2011 Arab Uprisings - Ihab Shabana (Chrześcijaństwo-Świat-Polityka)
This article presents a comparative study of political Islam in Egypt and Tunisia after the 2011 Arab uprisings. The study offers a comparative analysis of the Egyptian Muslim Brotherhood’s (MB) and Tunisian Ennahda’s governance and practices in their respective countries. An insight on theoretical debates and ideological transformations across political Islam’s ideology is offered, while exploring the pathways towards political moderation. By comparatively investigating various sectors, such as politics, ideology, and social agendas, differentiated political Islam trajectories are uncovered and highlighted. Specifically, MB’s and Ennahda’s attainments, pitfalls, limitations, and the reasons behind their successes and failures, are presented. Furthermore, despite their “demise”, this article explores important strategies of survival, especially for the Egyptian MB.